PENGARUH PEMAHAMAN PAJAK UMKM TERHADAPTINGKAT KEPATUHAN WAJIB PAJAK UMKM - Fanny Jitmau; Jessika Jamaica Wanggay (Jurnal Pitis AKP, 2024)
This research discusses the influence of the implementation of UMKM tax on the level of compliance of UMKM taxpayers, with the formulation of the problem in this research being whether understanding UMKM tax has an effect on the level of compliance of UMKM taxpayers. The aim of this research is to determine whether MSME tax understanding has an influence on the level of compliance of UMKM taxpayers. The methodology used includes Quantitative Motodologo. This research uses data collection techniques: library research, documentation, and questionnaires. The data used is primary data. The research results show that understanding UMKM taxes has a very significant influence on the level of taxpayer compliance in Sorong City.